Genetic Variation within a Neutralizing Domain on the Haemagglutinin—Neuraminidase Glycoprotein of Newcastle Disease Virus - Iorio, Ronald M.; Borgman, Jody B.; Glickman, Rhona L.; Bratt, Michael A. (Journal of General Virology, 1986)
Summary Previously, a panel of monoclonal antibodies recognizing epitopes in four antigenic sites on the haemagglutinin—neuraminidase (HN) glycoprotein of the Australia-Victoria strain of Newcastle disease virus were used in strain comparisons. Epitopes in three sites were found to be conserved while the epitope recognized by the single antibody to site 3 was not. A new panel of antibodies is described, two of which bind to epitopes in site 3 and six of which bind to a site (site 1,4) that overlaps with sites 1 and 4 as determined by analyses of variants, temperature-sensitive mutants, and strains by assays of neutralization of infectivity and binding in a radioimmunoassay. Neutralization of heterologous strains with the panel of antibodies revealed that both new site 3 epitopes are also highly divergent, while three additional epitopes outside site 3 (those in site 1,4) are highly conserved. The new site 3 antibodies can bind to virions of several heterologous strains without neutralizing infectivity. Thus, of the 10 epitopes we have now examined, all of three in site 3 are specific with respect to neutralization of infectivity for th ehomologous strain, while all of seven in other sites are conserved in heterologous strains. This suggests that the strain specificity originally described for a single site 3 epitope is, instead, a property of a much more extensive, poorly conserved domain on the HN molecule.
Keywords: NDV